Update on Jehovah's Witness cases before the European Court of Human Rights: implications of a surprising partnership. Issue 3 (2nd October 2017) - Richardson, James T.
ABSTRACT: This contribution details the large number of cases carried by Jehovah's Witnesses to the European Court of Human Rights during its existence, and examines the many positive outcomes of those cases for the Witnesses and for religious freedom in the Council of Europe region. There is also discussion of theoretical debates concerning the underlying philosophy of the Court as it adjudicates the many religion cases the Witnesses have brought, and concepts from the sociology of law such as 'courts as partners' and 'third party partisans' also are examined as possible explanations of how the long-term and surprising arrangement has evolved over the life of the Court.